Assessment of children's and caregivers' preferences for treatments for escape‐maintained problem behavior. Issue 3 (26th March 2021) - Owen, Todd M.; Luczynski, Kevin C.; Rodriguez, Nicole M.; Fisher, Wayne W.
Abstract : This study assessed children's and caregivers' preferences for various arrangements of negative reinforcement, including differential negative reinforcement of an alternative behavior (DNRA), noncontingent escape (NCE), and escape extinction. In the first treatment comparison, the DNRA and NCE treatments similarly decreased problem behavior, but all 3 children preferred DNRA. By contrast, 3 of 4 caregivers preferred escape extinction, likely due to increased compliance in this condition. In a second treatment comparision with 1 child, a multiple schedule and then a chained schedule were introduced to increase the practically of the initial DNRA treatment. The child continued to prefer the treatment with contingent reinforcement in both comparisons, and his caregivers preferred the chained schedule. Results further support the selection of treatments that include contingent reinforcement, and the evaluation serves as a model for progressing through treatment options until child and caregiver preferences align.